Strain rate dependency of bovine trabecular bone under impact loading at sideways fall velocity. (25th June 2018) - Enns-Bray, William S.; Ferguson, Stephen J.; Helgason, Benedikt
Abstract: There is currently a knowledge gap in scientific literature concerning the strain rate dependent properties of trabecular bone at intermediate strain rates. Meanwhile, strain rates between 10 and 200/s have been observed in previous dynamic finite element models of the proximal femur loaded at realistic sideways fall speeds. This study aimed to quantify the effect of strain rate ( ε ̇ ) on modulus of elasticity (E), ultimate stress (σu ), failure energy (Uf ), and minimum stress (σm ) of trabecular bone in order to improve the biofidelity of material properties used in dynamic simulations of sideways fall loading on the hip. Cylindrical cores of trabecular bone (D = 8 mm, Lgauge  = 16 mm, n = 34) from bovine proximal tibiae and distal femurs were scanned in µCT (10 µm), quantifying apparent density ( ρ app ) and degree of anisotropy (DA), and subsequently impacted within a miniature drop tower. Force of impact was measured using a piezoelectric load cell (400 kHz), while displacement during compression was measured from high speed video (50, 000 frames/s). Four groups, with similar density distributions, were loaded at different impact velocities (0.84, 1.33, 1.75, and 2.16 m/s) with constant kinetic energy (0.4 J) by adjusting the impact mass. The mean strain rates of each group were significantly different (p < 0.05) except for the two fastest impact speeds (p = 0.09). Non-linear regression models correlated strain rate, DA, and ρ app with ultimate stress (R 2  = 0.76), elastic modulus (R 2  = 0.63), failure energy (R 2  = 0.38), and minimum stress (R 2  = 0.57). These results indicate that previous estimates of σu could be under predicting the mechanical properties at strain rates above 10/s.